The Potential of Business Environment Institutions and the Support for the Development of Small and Medium-sized Enterprises - Renata Lisowska (Entrepreneurial Business and Economics Review)
Objective: The paper aims to assess the use of the potential of business environment institutions to support SMEs in the light of the author's own research.